HOLEVO CAPACITY ANALYSIS ON TWO DEPOLARIZING CHANNEL IN A QUANTUM SWITCH - Cahyadi, Felix
We are currently experiencing the second quantum revolution, where quantum phenomena are finding their place in new technologies. One crucial example is quantum communication, which deals with transforming and transmitting quantum information. One of the main concerns in quantum communication is noise fighting, in which various methods are developed to deal with noises. This research investigated the application of a quantum switch for noise fighting. To do so, we used Holevo capacity to measure the maximum amount of information that can be transmitted reliably by the channels. We optimized the parameters of the input qubit for each noise type. Then, we determined the capacity profiles of each noise channel. Our results show that a quantum switch can preserve channel capacity better than its single-channel counterpart.